Assesment of bone healing after surgical management of odontogenic cysts utilizing fractal analysis—a retrospective cross-sectional study - Ayse Tas; Elif Celebi; Zeynep Çukurova Yilmaz (PeerJ, 2025)
Objectives Odontogenic cysts, originating from inflammatory or developmental processes of the tooth germ epithelium, represent the most common intraosseous pathology in the head and neck region. This retrospective study aimed to evaluate bone healing following the surgical removal of odontogenic cysts using fractal analysis. Materials and Methods Bone changes in 17 patients who underwent cyst enucleation were assessed using fractal dimension and lacunarity measurements on digital panoramic radiographs obtained before and six months after surgery. Statistical analyses included the Shapiro–Wilk test, paired t-test, Wilcoxon signed-rank test, repeated measures ANOVA, and the Friedman test. Results At six months postoperatively, bone structure differences had largely normalized. In the cyst center, there were no statistically significant differences in fractal dimension or lacunarity (P > 0.05). At the cyst edge, fractal dimension remained statistically unchanged (P = 0.446), while lacunarity significantly decreased from 0.06 to 0.04 (P = 0.04). In unaffected control regions, no significant changes were observed (P > 0.05). Preoperative fractal dimension values significantly differed between regions (P < 0.001), but these differences were no longer significant postoperatively (P = 0.077). Lacunarity values showed no significant regional differences at either time point (P > 0.05). Conclusions Fractal analysis offers valuable insights into bone regeneration and may surpass traditional radiographic evaluations. Despite limitations such as small sample size and potential subjectivity in region of interest (ROI) selection, the results support the utility of fractal dimension and lacunarity in tracking bone healing after cyst surgery.